Supplier Integration Practices and Production Capacity in Restaurant Enterprises, Kisumu City Kenya - Odhiambo, Patrick Onono; Nassiuma, Dr. Bernard Kibeti (International Journal of Supply Chain Management, 2017)
Purpose: Enterprise growth in restaurants is contingent to production capacity. Customers are the pillar to any enterprises growth hence, establishing a sustainable value delivery system can result in competiveness and entrepreneurial sustainability. Igniting customer demand in restaurant enterprises is critical in sustaining sales growth. This study was based on the resource - based and competence -based theories. Methodology: The study was based on a sample size of 120 participants. Who comprised of owners and employees, who completed a self-administered questionnaire. Data analysis was based on Pearson correlation test. Findings: The findings show that supplier Intergration had a positive relationship with the production capacity. The key findings reveal that production capacity had a positive and significant relationship with integration of supplier base. Conclusion and policy recommendations: The study concludes that integration of supplier base influences enhancement of production capacity hence, igniting enterprise growth. The study recommends SEs to focus on developing efficient and effective entrepreneurial competencies on the supplier base integration.